Channels and Tools of Marketing Communication Strategy - Veronika OLEXOVA; Lubica GAJANOVA (Communications of International Proceedings, 2020)
The current market environment is characterized by strong competition between companies. Therefore, if companies want to succeed in the market, they must constantly work to set and achieve their goals. The process by which an effective business operates is called a marketing strategy. A marketing strategy can be implemented by a combination of different tools. The goals that the company wants to achieve are important. If a company wants to be successful, it must create a certain position in the market and must also focus its activities on current as well as potential customers. Satisfying customer needs is the main task of marketing and is achieved through a marketing mix that represents the integration of 4 elements. One of the tools of the marketing mix is communication, which is important especially because it ensures the addressing of customers and the promotion of products as well as the entire company. The aim of the article is to point out the theoretical basis of marketing strategy with emphasis on its tools and channels. The practical part is focused on the analysis of secondary data with a focus on consumer preferred channels of brand communication during the coronavirus pandemic worldwide.
Keywords: Communication; Channels; Marketing; Strategy; Tools.